Stop the administrative dispute (Damascus University Journal for legal sciences, 2026)
Administrative proceedings are a right given to natural and legal persons to have recourse to the courts with a view to obtaining a judgement on the subject of the dispute to protect their abused rights by revoking legal action by the administration or compensating for damages suffered by them.An administrative action is the legal authority that can be granted within the set of legal rules to claim protection of a fundamental right or interest as a result of an infringement of that right by unlawful administrative acts and to demand their removal and compensation for damages resulting therefrom.The litigation commences from the time of the filing of the case sheet until a judicial judgement has been issued determining the dispute between them or the expiration of the case without a judgement in the matter.However, this adversarial process may be intercepted by factors and events leading to the discontinuation of administrative litigation.That is, not to proceed within a certain period of time if a ground for suspension is considered by the court or the law
Keywords: Administrative Litigation; Legal Suspension; Judicial Suspension; The Expiration Of The Litigation; The Symptoms Of The Lawsuit.